Unified description of the DC conductivity of monolayer and bilayer graphene based on resonant scatterers - Ferreira, Aires (2011)
We show that a coherent picture for the DC conductivity of monolayer and bilayer graphene emerges from considering that strong short-range potentials are the main source of scattering in these two systems. The origin of the strong short range potentials may lie in adsorbed hydrocarbons at the surface of graphene. The equivalence between results based on the partial wave description of scattering and the T-matrix approach is established. The scattering formalism for electrons in a biased bilayer graphene is developed and the DC conductivity of that system is studied.